INTRINSIC ELEMENTS OF “BULAN TERBELAH DI LANGIT AMERIKA” THE NOVEL - Rika Lestari; Retno Fitriani; Dinda Nurlaili; Lutfi Nuraini Ismaiyah; Kevin Fawaizul Umam; Bayu Bimantara (JOSAR (Journal of Students Academic Research), 2017)
One of literary works in novel that are phenomenal is novel entitled “Bulan Terbelah di Langit Amerika”. This novel was written by Hanum Salsabiela Rais and Rangga Almahendra. It was published by Gramedia Pustaka Utama in 2004. This novel reveals the mystery of 11 September or often called black Tuesday. This research was motivated by desire to find the intrinsic elements. The problems in this research is how is the character, theme, plot, point of view, setting, conflict, and tone in “Bulan Terbelah di Langit Amerika” Novel. This research used descriptive qualitative method with literature approach. The source of this research is part of the text in the novel. Technique of data collecting used analysis of the novel. This novel is not only gives entertainment but also inculcate religious value that easily understood and implemented by the reader in everyday life. “Bulan Terbelah di Langit Amerika” can be used as an example to convert the novel into film or drama. Then, the novel can also be used as teaching materials viewed from the aspects of language, psychology, and cultural background. The result of this study can be implemented in Introduction to Literature learning in analyzing the intrinsic elements of the novel.